2021
DOI: 10.1167/iovs.62.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Macular Retinal and Choroidal Microvasculature Changes in High Myopia

Abstract: Purpose The purpose of this study was to determine the longitudinal changes in macular retinal and choroidal microvasculature in normal healthy and highly myopic eyes. Methods Seventy-one eyes, including 32 eyes with high myopia and 39 healthy control eyes, followed for at least 12 months and examined using optical coherence tomography angiography imaging in at least 3 visits, were included in this study. Fovea-centered 6 × 6 mm scans were performed to measure capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
5
9
0
Order By: Relevance
“…[32][33][34][35] A longitudinal study by Lin et al showed that the rate of CD loss in DCP was signi cantly faster in the HM group than that in the normal control group, whereas the rates of CD loss in SCP were similar between the two groups, which is in agreement with our ndings. 32 Our study revealed that a reduction in the retinal microvasculature in myopic eyes occurred mainly in the peripheral retina beyond the 6 × 6 mm² area among patients with an AL >28 mm. Our ndings were in agreement with those of the study by Jonas et al, which reported that peripheral retinal thinning was associated with longer AL, but macular retinal thinning was not; this supported the notion that myopic enlargement of the globe occurs predominantly by axial elongation of the globe walls in the midperiphery.…”
Section: Discussionsupporting
confidence: 92%
“…[32][33][34][35] A longitudinal study by Lin et al showed that the rate of CD loss in DCP was signi cantly faster in the HM group than that in the normal control group, whereas the rates of CD loss in SCP were similar between the two groups, which is in agreement with our ndings. 32 Our study revealed that a reduction in the retinal microvasculature in myopic eyes occurred mainly in the peripheral retina beyond the 6 × 6 mm² area among patients with an AL >28 mm. Our ndings were in agreement with those of the study by Jonas et al, which reported that peripheral retinal thinning was associated with longer AL, but macular retinal thinning was not; this supported the notion that myopic enlargement of the globe occurs predominantly by axial elongation of the globe walls in the midperiphery.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the deep parafoveal VD was found to be significantly associated with AL ( 17 ). Similar results were also found by Lin et al, indicating that only the VD of the DCP showed a significant reduction, whereas the VD of the SVP showed no significant changes in high myopic eyes ( 41 ). Their results were consistent with our study results, which reported that the VD of the DCP was significantly lower in the myopia group than in the hyperopia group, whereas no significant VD of SVP differences was observed among the hyperopia, emmetropia, and myopia groups.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, DCP is reported to be difficult to recover from injury, which could also explain the significant decrease in the VD of DCP in myopia ( 23 , 45 , 46 ). This difference between DCP and SVP was also supported by the study of Lin et al, reporting that VD loss in the DCP was significantly faster in the high myopia group than in the normal group, whereas the rate of VD loss in the SVP was equal in high myopia and normal groups ( 41 ). Moreover, a previous study reported that VD of DCP changed significantly with aging, whereas VD of SVP remained relatively unchanged ( 13 ), indicating that VD of DCP could be more vulnerable to external influence factors than VD of SVP.…”
Section: Discussionsupporting
confidence: 60%
“… 27 High myopia was also associated with reduced vessel diameters at the retinal posterior pole and accelerated capillary density loss. 4 , 28 Therefore, the presence of a cilioretinal artery may provide additional blood flow and oxygen to the macula, 29 resulting in potential preservation of macular functions. 12 However, previous evaluations based on VA assessment only partially assessed its effects on functional vision.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Due to the elongation of axial length (AL) of the eye and extreme thinning of the choroid and retina, the fundus vasculature of highly myopic eyes is reportedly attenuated and may negatively impact macular functions. 3 , 4 Exploring and identifying potential protective factors for macular functions may help preserve vision in eyes with high myopia.…”
mentioning
confidence: 99%